An Antioxidant Marker, Aminolevulinic Acid Dehydratase, was Correlated with Bone Turnover Activity - Mulyana Mulyana; Mansyur Arif; Dewi Muliaty (The Prodia Education and Research Institute (PERI), 2012)
BACKGROUND: Recent studies have indicated that lead may affect activities on bone cells, but the mechanism is not yet clear. Therefore, we conducted a study to investigate correlation of chronic low-concentration lead exposure with bone turnover activity (ratio of C-telopeptide (CTx) and Procollagen Type 1 Amino-terminal Propeptide (P1NP) (CTx/P1NP)) and antioxidant (aminolevulinic acid (ALA) dehydratase (ALAD)) in a workers community. METHODS: An observational study with cross-sectional design was carried out. Fifty two subjects from a workers community in Jakarta, Indonesia, had provided informed consents and undergone medical history, physical and laboratory examinations. Hair lead concentration was measured by Inductively Coupled Plasma Mass Spectrometry (ICP-MS) method. Meanwhile, P1NP was measured by Enzyme-linked immunosorbent assay (ELISA) and CTx was measured by Electro-chemiluminescence Immunoassay (ELICA) method. RESULTS: The mean hair lead concentration was 4.85 ppm. Based on Mayo Clinic reference, 28.85% of investigated subjects had hair lead concentration of ≥5 ppm. Hair lead concentration was not correlated with ALAD, CTx, P1NP concentrations or CTx/P1NP. ALAD concentration was significantly correlated with CTx/P1NP (p<0.05; r=0.35).SUMMARY: ALAD concentration was correlated with CTx/P1NP ratio, indicating that the role of antioxidant was possibly caused by accumulated chronic low-concentration lead exposure, which was correlated with bone turnover activity. KEYWORDS: hair lead, ALAD, CTx, P1NP, osteoporosis, bone turnover